Realistic 3D Object Visualization in Early Childhood Educational Games Using Ray Tracing Algorithms - Moh. Ainol Yaqin Yaqin; Abu Tholib; Juvinal Ximenes Guterres (JOKI: Jurnal Komputasi dan Informatika, 2025)
Computer graphics plays a crucial role in creating engaging and interactive learning experiences for young children. This study implements ray tracing algorithms to enhance 3D object visualization in educational games designed for early childhood. The objective is to improve visual realism, thereby increasing children's interest and engagement in learning through interactive gameplay. The game was developed using C++ and OpenGL, incorporating ray tracing techniques to simulate light behavior accurately and produce realistic shading and reflections. The research followed a systematic development process, including literature review, game design, algorithm implementation, and user evaluation. The evaluation, involving early learners, showed a significant increase in attention span, comprehension, and enthusiasm among children exposed to ray-traced 3D environments, compared to traditional visualization techniques. These findings suggest that realistic 3D visualization through ray tracing can be a valuable asset in educational media, supporting cognitive development and learning motivation in early childhood education.